2009
DOI: 10.1111/j.1365-294x.2009.04266.x
|View full text |Cite
|
Sign up to set email alerts
|

In situpopulation structure andex siturepresentation of the endangered Amur tiger

Abstract: The Amur tiger (Panthera tigris altaica) is a critically endangered felid that suffered a severe demographic contraction in the 1940s. In this study, we sampled 95 individuals collected throughout their native range to investigate questions relative to population genetic structure and demographic history. Additionally, we sampled targeted individuals from the North American ex situ population to assess the genetic representation found in captivity. Population genetic and Bayesian structure analyses clearly ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
122
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 60 publications
(134 reference statements)
7
122
0
Order By: Relevance
“…In the present study, we found slightly higher levels of observed heterozygosity and average number of alleles per locus in captivity relative to the wild C. rhombifer population (Table 1), including a large number of private alleles. These differences in the extent and distribution of in situ and ex situ genetic variation could be indicative of gene variants retained in the captive population that are now extirpated in the wild, as has been found in other critically endangered species (Henry et al, 2009). Alternatively, this pattern may have been influenced by long-term introgression with C. acutus in captivity dating back to the early years of the breeding program.…”
Section: Hybridization Between Cuban and American Crocodilesmentioning
confidence: 99%
“…In the present study, we found slightly higher levels of observed heterozygosity and average number of alleles per locus in captivity relative to the wild C. rhombifer population (Table 1), including a large number of private alleles. These differences in the extent and distribution of in situ and ex situ genetic variation could be indicative of gene variants retained in the captive population that are now extirpated in the wild, as has been found in other critically endangered species (Henry et al, 2009). Alternatively, this pattern may have been influenced by long-term introgression with C. acutus in captivity dating back to the early years of the breeding program.…”
Section: Hybridization Between Cuban and American Crocodilesmentioning
confidence: 99%
“…Tigers in Southwest Primorye are separated from the main tiger population in the Sikhote-Alin Mountains by a development corridor between the two major cities of Vladivostok and Ussuriysk (Darman & Williams, 2003;Miquelle et al, 2015). This anthropogenic barrier has limited dispersal of large carnivores and resulted in a genetically distinct tiger population in southwest Primorye (Henry et al, 2009;Sorokin et al, 2015). Although a few migrants from southern SikhoteAlin have been identified in southwest Primorsky Krai, it is still unknown whether these occasional migrants have successfully contributed to the gene pool of the southwestern sub-population (Henry et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This anthropogenic barrier has limited dispersal of large carnivores and resulted in a genetically distinct tiger population in southwest Primorye (Henry et al, 2009;Sorokin et al, 2015). Although a few migrants from southern SikhoteAlin have been identified in southwest Primorsky Krai, it is still unknown whether these occasional migrants have successfully contributed to the gene pool of the southwestern sub-population (Henry et al, 2009). Further disruption of tiger movements between two landscapes may have serious consequences for genetic health of the smaller group of tigers, and limits the potential for expansion of the leopard population.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the helminths presence in the Amur tiger excrements collected in the south, center and north of its range suggests that helminth fauna has certain particularities in different parts of the tiger habitat, with about the same proportion of samples with eggs of helminths found. So, in the Amur tiger population in the Southwest of Primorskii Kray that is considered isolated 11,38 , two specific parasites were discovered (nematoda Aelurostrongylus abstrusus and cestoda Spirometra erinacei). Nematoda Toxocara cati, found in virtually all excrement samples, is the most common species in all parts of the Amur tiger habitat.…”
Section: Resultsmentioning
confidence: 99%